The Pengaruh Model Pembelajaran POE (Predict, Observe, Explain) Terhadap Hasil Belajar Kimia Materi Asam Basa Pada Siswa Kelas XI SMAN 1 Langgudu - Nurkamaliah Lia; Jeckson Siahaan; Mukhtar Haris (Chemistry Education Practice, 2025)
This study aims to determine the effect of POE (Predict, Observe, Explain) learning model on chemical learning outcomes of acid-base material in class XI IPA SMAN 1 Langgudu. This type of research is a quasi experimental design. The population is all students of class XI IPA SMAN 1 Langgudu which amounted to 50 people. The sampling technique used saturated sampling. Determination of control and experimental classes is based on the average value of the midterm assessment, students of class XI IPA 1 obtained a greater average value of 78.76 than class XI IPA 2 which is 70.16 so that class XI IPA 1 is designated as the control class and XI IPA 2 as the experimental class. Data collection techniques using test instruments. The average value of the experimental class pretests (49.12) was lower than the control class (52.28). While the average value of the experimental class posttest (84.4) is higher than the control class (76.92). The N-Gain test results show that the increase in learning outcomes of experimental class students is more in the high category than the control class. The t-test results obtained tcount of 2.4091> ttable 2.0106 then H0 is rejected and Ha is accepted. While the results of the percentage of student activeness of the experimental class at each meeting were higher than the control class, so that experimental class students were more active than the control class. The results of this study can be concluded that the POE learning model (Predict, Observe, Explain, and Explain) is an effective learning model.